Does climate change alter the nutrient trends of Cedrela fissilis Vell. trees in the southern Brazilian Amazon? - Ortega Rodriguez, Daigard R.; Sánchez-Salguero, Raúl; Hevia, Andrea; Bovi, Renata C. [UNESP]; Ferreira, Marciel J.; Speer, James H.; Roig, Fidel A.; Tomazello-Filho, Mario (Springer Nature, 2023)
Background: The increase in the frequency and intensity of droughts is pointed out as one of the main factors altering biogeochemical cycles in the Amazon basin. An eco-nutritional approach using X-ray fluorescence micro-analysis (µXRF) is proposed to verify the long- and short-term effects of droughts on the growth and xylem nutrient concentrations of Cedrela fissilis Vell. Methods: Fourteen radii were selected from a tree-ring width chronology and X-rayed by Itrax Multiscanner. Profiles of ring width, wood density, and concentrations of aluminum (Al), phosphorus (P), sulfur (S), calcium (Ca), potassium (K), manganese (Mn), iron (Fe) and strontium (Sr) together with Al/Ca, Ca/Mn, K/Ca, Sr/Ca and Mn/S ratios were constructed and correlated with precipitation, temperature, the difference between precipitation and potential evapotranspiration (P-PET) and standardized precipitation–evapotranspiration index (SPEI). Results: During dry years, C. fissilis showed narrower, less dense rings, lower Al, P, S and Ca, and higher K and Fe concentrations (the opposite was found in wet years). Ring width decreased (together with Al, P, S, K, Ca, Mn, Fe, Sr, Al/Ca, K/Ca and Sr/Ca) and wood density increased (together with Ca/Mn and Mn/S), which was associated with an increase in evapotranspiration and temperature over time, mainly since 1990. Cedrela fissilis showed a tendency to increase its capacity for resistance, and a recovery and resilience in growth over time associated with responses in Al, Ca, P and S. However, it showed a risk in the capacity for recovery of the pre-drought density values, associated with unsatisfactory responses in Al, Ca, K, Fe and P. Conclusions: This study is the first attempt to analyze tree-ring nutritional evidences of C. fissilis trees to climate sensitivity and resilience to drought, based on long-term data from seasonal moist tropical forests of the Amazon. Our data suggested that C. fissilis is undergoing alterations in the concentration, use and redistribution of nutrients associated with increasing wood density and decreasing growth over time, due to the increase of drought frequency in the southern Amazon.
Keywords: Dendrochemistry; Drought; Eco-chemical indicator; Recovery; Resilience; Resistance; Tropical tree; µXRF